The Wobbler Mouse Model of Amyotrophic Lateral Sclerosis (ALS) Displays Hippocampal Hyperexcitability, and Reduced Number of Interneurons, but No Presynaptic Vesicle Release Impairments - Thielsen, Karina D. (Public Library of Science, 2013)
Amyotrophic lateral sclerosis (ALS) is the most common adult-onset motor neuron disease. It is a fatal degenerative disease, best recognized for its debilitating neuromuscular effects. ALS however also induces cognitive impairments in as many as 50% of affected individuals. Moreover, many ALS patients demonstrate cortical hyperexcitability, which has been shown to precede the onset of clinical symptoms. The wobbler mouse is a model of ALS, and like ALS patients the wobbler mouse displays cortical hyperexcitability. Here we investigated if the neocortical aberrations of the wobbler mouse also occur in the hippocampus. Consequently, we performed extracellular field excitatory postsynaptic potential recordings in the CA1 region of the hippocampus on acute brain slices from symptomatic (P45-P60) and presymptomatic (P17-P21) wobbler mice. Significant increased excitation of hippocampal synapses was revealed by leftward shifted input/output-curves in both symptomatic and presymptomatic wobbler mice, and substantiated by population spike occurrence analyses, demonstrating that the increased synaptic excitation precedes the onset of visible phenotypic symptoms in the mouse. Synaptic facilitation tested by paired-pulse facilitation and trains in wobbler and control mice showed no differences, suggesting the absence of presynaptic defects. Immunohistochemical staining revealed that symptomatic wobbler mice have a lower number of parvalbumin positive interneurons when compared to controls and presymptomatic mice. This study reveals that the wobbler mouse model of ALS exhibits hippocampal hyperexcitability. We suggest that the hyperexcitability could be caused by increased excitatory synaptic transmission and a concomitant reduced inhibition due to a decreased number of parvalbumin positive interneurons. Thus we substantiate that wobbler brain impairments are not confined to the motor cortex, but extend to the hippocampus. Importantly, we have revealed more details of the early pathophysiology in asymptomatic animals, and studies like the present may facilitate the development of novel treatment strategies for earlier intervention in ALS patients in the future.